The North American Neuroendocrine Tumor Society Consensus Guidelines for Surveillance and Medical Management of Midgut Neuroendocrine Tumors. Issue 6 (July 2017) - Strosberg, Jonathan R.; Halfdanarson, Thorvardur R.; Bellizzi, Andrew M.; Chan, Jennifer A.; Dillon, Joseph S.; Heaney, Anthony P.; Kunz, Pamela L.; O'Dorisio, Thomas M.; Salem, Riad; Segelov, Eva; Howe, James R.; Pommier, Rodney F.; et al.
Abstract : Abstract: There have been significant developments in diagnostic and therapeutic options for patients with neuroendocrine tumors (NETs). Key phase 3 studies include the CLARINET trial, which evaluated lanreotide in patients with nonfunctioning enteropancreatic NETs; the RADIANT-2 and RADIANT-4 studies, which evaluated everolimus in functioning and nonfunctioning NETs of the gastrointestinal tract and lungs; the TELESTAR study, which evaluated telotristat ethyl in patients with refractory carcinoid syndrome; and the NETTER-1 trial, which evaluated 177 Lu-DOTATATE in NETs of the small intestine and proximal colon (midgut). Based on these and other advances, the North American Neuroendocrine Tumor Society convened a multidisciplinary panel of experts with the goal of updating consensus-based guidelines for evaluation and treatment of midgut NETs. The medical aspects of these guidelines (focusing on systemic treatment, nonsurgical liver-directed therapy, and postoperative surveillance) are summarized in this article. Surgical guidelines are described in a companion article.